Effect of anxiolytic and hypnotic drug prescriptions on mortality hazards: retrospective cohort study - Weich, Scott (BMJ Publishing Group Ltd., 2014)
Objective To test the hypothesis that people taking anxiolytic and hypnotic drugs are at increased risk of premature mortality, using primary care prescription records and after adjusting for a wide range of potential confounders. Design Retrospective cohort study. Setting 273 UK primary care practices contributing data to the General Practice Research Database. Participants 34 727 patients aged 16 years and older first prescribed anxiolytic or hypnotic drugs, or both, between 1998 and 2001, and 69 418 patients with no prescriptions for such drugs (controls) matched by age, sex, and practice. Patients were followed-up for a mean of 7.6 years (range 0.1-13.4 years). Main outcome All cause mortality ascertained from practice records. Results Physical and psychiatric comorbidities and prescribing of non-study drugs were significantly more prevalent among those prescribed study drugs than among controls. The age adjusted hazard ratio for mortality during the whole follow-up period for use of any study drug in the first year after recruitment was 3.46 (95% confidence interval 3.34 to 3.59) and 3.32 (3.19 to 3.45) after adjusting for other potential confounders. Dose-response associations were found for all three classes of study drugs (benzodiazepines, Z drugs (zaleplon, zolpidem, and zopiclone), and other drugs). After excluding deaths in the first year, there were approximately four excess deaths linked to drug use per 100 people followed for an average of 7.6 years after their first prescription. Conclusions In this large cohort of patients attending UK primary care, anxiolytic and hypnotic drugs were associated with significantly increased risk of mortality over a seven year period, after adjusting for a range of potential confounders. As with all observational findings, however, these results are prone to bias arising from unmeasured and residual confounding.